Сучасні підходи до аналізу кредитоспроможності позичальників: український та світовий досвід - Khomenko, Inna; Sadchykova, Iryna; Krasnianska, Yuliia (Dr. Viktor Koval, 2019)
Introduction. Non-repayment of loans by borrowers not only jeopardizes the profitability of banking structures, but also the ability to calculate them under liabilities - deposit and borrowed funds. This situation is dangerous for the entire banking sector of the country, as it raises a number of acute problems: imbalance of loan and deposit portfolio by volumes and terms; distrust of the population to commercial banks, financial destabilization in the state as a whole, and others like that. Aim and tasks. The main purpose of this work is to study modern domestic and foreign approaches to assessing the creditworthiness of borrowers. Results. Based on the analysis of the definitions it is expedient to use the following interpretation of the term "creditworthiness": the financial, economic and legal capacity of the borrower to obtain a loan and return it to the commercial bank in accordance with the terms and conditions of the agreement. At the initial stages of the methodologies developing for the analysis of borrowers' lending, the leading role was played by the coefficient method, which by its nature is considered the simplest and is currently used as an express evaluation and preceded by other research. Currently, almost all commercial banks use a rating approach to assess the borrower's creditworthiness. Such methods also include calculation of coefficients, but contain a predictive component. The rating approach is valuable, because it requires a constant collection of updated information. Often, banks when building credit ratings use the methods of the relevant agencies. It is now believed that the formation of credit ratings allows you to get the most general idea of the borrower's creditworthiness (at the level of the commercial bank) and about the quality of the loan portfolio (at the level of the banking system of the state). Moreover, when assessing the creditworthiness of borrowers – individuals, the rating approach is most often used. Conclusions. The conducted studies indicate that improving approaches to assessing the creditworthiness of borrowers by commercial banks is particularly relevant for Ukraine. It is important to carry out measures (including administrative) in order to increase the reliability of the input information of borrowers, training of specialized specialists – experts, assessment of qualitative data on the debtor, formation of constantly updated statistical databases, adjustment of methodological developments taking into consideration the variability of the economic situation in Ukraine, ensuring transparency of the analysis, etc.